The composite microbial agent controls tomato bacterial wilt by colonizing the root surface and regulating the rhizosphere soil microbial community - Zhu, Shuangxi; Chang, Xiaojian; Liu, Nana; He, Yanhui; Wang, Jianwen; Wu, Zhansheng (Frontiers in Microbiology, 2025)
IntroductionBacterial wilt caused by Ralstonia solanacearum seriously affects the healthy growth of tomato seedlings. Biocontrol microbes have been used to manage tomato bacterial wilt. Herein, we aim to investigate the behavior of the Enterobacter hormaechei Rs-5 and Bacillus subtilis SL-44 composite microbial agent (EB) in the rhizosphere soil, and assess its impact on both the soil microbial community and tomato plant growth in this study.MethodsThe plate confrontation experiment and the pot experiment were respectively used to explore the control ability of EB against Ralstonia solanacearum and bacterial wilt disease. The absolute quantitative PCR (AQ-PCR) was employed to investigate the migration ability of EB in the rhizosphere of tomatoes, and the chemotactic response of EB to tomato root exudates was analyzed by the swimming plate method. Scanning electron microscopy was utilized to study the biofilm formation of EB during its colonization on the root surface of tomatoes. Finally, high-throughput sequencing was adopted to analyze the impact of EB on the microbial community in the rhizosphere soil of tomatoes after being infected by Ralstonia solanacearum.ResultsThe absolute quantitative PCR and scanning electron microscope showed that the EB could migrate and efficiently colonize the elongation zone of tomato roots to form a biofilm. In addition, the EB exhibits a chemotactic response to tomato root exudates like sucrose, leucine, glutamic acid, and aspartic acid. The pot experiment demonstrated that the EB can reduce the incidence of tomato bacterial wilt from 77.78% to 22.22%, and significantly increase the biomass, physicochemical properties, and rhizosphere soil nutrient contents of tomato seedlings. Besides, the relative abundance of beneficial bacteria such as Massilia, Pseudomonas, Bacillus, and Enterobacter increased, and the fungi community diversity was improved.ConclusionOverall, the EB can reduce the amount of Ralstonia solanacearum in rhizosphere soil, and then control tomato bacterial wilt directly. Besides, the EB can migrate to the root under the induction of tomato root exudates and colonize on the root surface efficiently, thereby indirectly regulating the soil microbial community structure and controlling tomato bacterial wilt.